Loop-Mediated Isothermal Amplification (LAMP) for Detection of Various Organisms: A Review - Akram, Arifa (Bangladesh Journal of Medical Microbiology, 2017)
Disease diagnosis is important for implementation of proper therapeutic and prophylactic measures. Traditionally, disease diagnosis was depends upon isolation and identification of the causative organisms. This was followed by serology and after that molecular method. Molecular tests are valuable when early diagnosis is important. For this purpose, nucleic acid amplification (PCR, nucleic acid sequence-based amplification, self-sustained sequence replication, strand displacement amplification) is one of the most valuable tools not only for the diagnosis of infectious diseases but also used in advanced level research. The Loop-Mediated Isothermal Amplification (LAMP) is a unique nucleic acid amplification technique for diagnosis of various pathogens introduced at 2000 by Notomi and his colleagues which is simple, easy, rapid and cost effective when compared to PCR due to its high specificity, sensitivity, and rapidity. It uses a set of six primers and a DNA polymerase with stranddisplacement activity. Major advantage of LAMP method is its cost-effectiveness as it can be done simply by using waterbath or heating block. Bangladesh J Med Microbiol 2017; 11 (2): 20-27